Students' Perception Of News Text LKPD (Student Wokrsheet) in Grade XI F-4 SMAS Adabiah 2 Padang - Syahra Nadilla Sanjaya; Sofina Putri; Frizynia Putri Nabila; Yulianti Rasyid; Dadi Satria (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to determine the perceptions of Grade XI F-4 students at SMA Adabiah 2 Padang regarding the News Text Worksheet (LKPD) developed. This study employed a quantitative descriptive approach. The research model used was a survey with an online questionnaire as the research instrument. After data collection, steps were carried out based on a Likert Scale, such as summing the questionnaire responses, calculating the minimum total, calculating the maximum total, determining the range, calculating the length of the interval value class, and categorizing. The results of this study revealed a highly positive perception among grade XI F-4 students regarding the News Text Worksheet, with 89.25% rating ease of use, 88% rating time efficiency, 91.5% rating readability, 84.5% rating difficulty level, and 89.25% rating independence. Furthermore, complaints regarding the News Text Worksheet included limited time (duration) for completing the worksheet and limited information presented.